Examining the Validity of Constructs that Measure the Willingness to Share Waqf Information: An Exploratory Factor Analysis - Noraini binti Yusuff; Fuadah Johari; Hanim Hj Misbah; Nurul Adilah Hasbullah; Azuan Ahmad; Nor Syahidah binti Ishak; Siti Latipah binti Harun; Siti Hajar Salwa binti Ahmad Musadik (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
10th INTERNATIONAL ISLAMIC ECONOMIC SYSTEM CONFERENCE 2023 (I-iECONS 2023) : “Sustainable Development through Innovative Economic Transformation” /Editors : Amalina Mursidi, Agoos Munalis Tahir, Suhaida Herni Suffarruddin, Norfhadzilawati Rahim, Murad Ali Ahmad Al-Zaqeba, Muhammad Iqmal Hisham Kamaruddin Conference Dates: August 14 2023 | Conference Location: Millennium Makkah Al Naseem Hotel Mecca Saudi Arabia Organized by Faculty of Economics and Muamalat